Pyramidal and Proprioceptive Dysfunctions as the Main Neurologic Features In Symptomatic Type I Chiari Malformation Patients - Leimig, Bruno Corrêa de Albuquerque; Vidal, Claudio Henrique Fernandes; Valença, Marcelo Moraes; Silva, Joacil Carlos da; Matias Filho, Walter de Freitas (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Objective Broader access to magnetic resonance imaging (MRI) has increased the diagnosis of tonsillar ectopia, with most of these patients being asymptomatic. The early diagnosis and treatment of type I Chiari malformation (CM I) patients has impact on the prognosis. This study supplements information about the neurologic exam of symptomatic patients with CM I.Methods The sample was composed of 32 symptomatic patients with CM I diagnosed by a combination of tonsil herniation of more than 5 mm below the magnum foramen (observed in the sagittal T2 MRI) and at least one of the following alterations: intractable occipital headache, ataxia, upper or lower motor neuron impairment, sensitivity deficits (superficial and deep) or lower cranial nerves disorders.Results Occipital headache was the most frequent symptom (53.12%). During the physical exam, the most common dysfunctions were those from the pyramidal system (96.87%), followed by posterior cord syndrome (87.5%).Discussion In this study, patients became symptomatic around the fifth decade of life, which is compatible with previous descriptions. Patients with more than 2 years of evolution have worse responses to treatment. Occipital headache, symptoms in the upper limbs, gait and proprioceptive disorders are common findings in patients with CM I.Conclusion Deep tendinous reflexes and proprioception disorders were the main neurologic features found in symptomatic CM I patients.
Keywords: arnold-chiari malformation; neurologic examination; pyramidal tracts; proprioception; syringomyelia